The Effect of an Annona muricata Leaves Extract on Circulating Soluble Adhesion Molecules in Colon Carcinogenesis Model - Indrawati, Lili; Kusmardi, Kusmardi; Wiyanto, Marwito (The Indonesian Society for Digestive Endoscopy, 2023)
Background: Annona muricata leaves are used as traditional tea drink that is currently being studied on the developing effort of treating some types of cancers because they are known as anti-cancer. Motivated by that usage, this study aims to analyse the potential of A. muricata leaves extract to be an anti-colon cancer by investigating the extract capability in reducing blood intercellular cell-adhesion molecule-1 (ICAM-1) and vascular cell-adhesion molecule-1 (VCAM-1).Method: The research was conducted in Faculty of Medicine Universitas Indonesia with an experimental design. A. muricata leaves extract was tested in vivo. In vivo test was conducted to Swiss Webster mice induced with 10 mg/kg azoxymethane (AOM) and dextran sodium sulfate 1% (DSS). Statistical analysis used was SPSS.Results: EIFAM reduce the serum level of ICAM-1 and VCAM-1. EIFAM significantly reduce serum level of VCAM compare to ESFAM.Conclusion: Ethanol insoluble fraction of Annona muricata leaves water extract of is potential to be an anti-colon cancer proven by the extract capability to reduce ICAM-1 and VCAM-1.